Justice-Involved as Prisoners by the IRB: Regulation Without Protection. - Morales, Gianna; James, Jennifer; LeMasters, Katherine (American Journal of Bioethics, 2026)
This article examines the ethical challenges of applying federal research protections under 45 CFR 46 Subpart C—originally designed for incarcerated prisoners—to women under state surveillance but not formally incarcerated. It argues that extending these protections to such women leads to their exclusion from important health research, perpetuates stigma, and contributes to underrepresentation of justice-involved and marginalized populations, including pregnant women and their children. The article highlights how this overextension may reinforce research bias and harm participants by limiting access to critical health data and interventions. It advocates for ethical research approaches that prioritize participant-centered protections, engagement with justice-involved women, and equity-focused measures rather than blanket regulatory restrictions.